Utilization of Mental Health Care, Treatment Patterns, and Course of Psychosocial Functioning in Northern German Coronary Artery Disease Patients with Depressive and/or Anxiety Disorders - Westermair, Anna Lisa; Schaich, Anja; Willenborg, Bastian; Willenborg, Christina; Nitsche, Stefan; Schunkert, Heribert; Erdmann, Jeanette; Schweiger, Ulrich (Frontiers in Psychiatry, 2018)
Background: Comorbid mental disorders in patients with coronary artery disease (CAD) are common and associated with adverse somatic outcomes. However, data on utilization rates of mental health care and treatment efficiency are scarce and inconsistent, which we tried to remedy with the present preliminary study on Northern German CAD patients. Method: A total of 514 German CAD patients, as diagnosed by cardiac catheterization, were assessed using the Mini International Neuropsychiatric Interview and the Global Assessment of Functioning (GAF) scale. Results: Global utilization of mental health care since onset of CAD was 21.0 %. Depressive disorders, younger age and lower GAF at onset of CAD were associated with higher utilization rates, while anxiety disorders and gender were not. Lower GAF at onset of CAD, female gender and psychotherapy were positively associated with higher gains in GAF, while younger age and anxiety disorders were negatively associated. Conclusions: The majority of CAD patients with comorbid depression reported to have received adequate mental health treatment and seemed to have benefited from it. However, we found preliminary evidence of insufficiencies in the diagnosis and treatment of anxiety disorders in CAD patients. Further studies, preferably prospective and with representative samples, are needed to corroborate or falsify these findings and explore possible further mediators of health care utilization by CAD patients such as race, ethnicity and socio-economic status.